PENGARUH LATIHAN AGILITY WHEEL TERHADAP KEMAMPUAN FOOTWORK SISWAEKSTRAKURIKULER BULUTANGKIS SMA N 4 MALANG - Achmad Riva Die Meana Husaini Z.A; Supriyadi Supriyadi; I Nengah Sudjana (Universitas Negeri Malang, 2016)
Abstract: Based on preliminary results, the result that students mastery of basic techniques footwork badminton extracurricular SMA N (Public Senior High School) 4 Malang still not mastered this basic technique because of the tendency of coaches only use exercise patterns footsteps so that athletes feel bored and will have an impact on the less serious exercise. The purpose of this research is to improve the ability of footwork with a variety of exercises agility wheel so that athletes do not feel bored to exercise frequently given, in the hope the athletes can have the basic technique footwork great and more active in training sessions so as to facilitate understanding of the basic techniques of footwork and bolster the ability of footwork. This research includes into experimental research. The research design used One Group Pretest-Posttest Design. T-test result showed the result for 4.790 ≥ t-table 2,093 for significance level 5%, based on the research result, thus it could be concluded that there was an effect of agility wheel training to the footwork ability of badminton extracurricular student in SMA N (Public Senior High School) 4 Malang. For further research, it needs a research about badminton footwork using more various training or play and game training model in order to make it more interesting and fun and also variable control to make more valid result. Keywords:badminton, agility wheel, ability, footwork.